Liver transplant outcomes after ex vivo machine perfusion: a meta-analysis. Issue 12 (17th November 2021) - Liew, Belle; Nasralla, David; Iype, Satheesh; Pollok, Joerg-Matthias; Davidson, Brian; Raptis, Dimitri A
Abstract: Background: The pressure on liver-transplant programmes has expanded the usage of extended-criteria allografts. Machine perfusion may be better than conventional static cold storage (SCS) in alleviating ischaemia–reperfusion injury in this setting. Recipient outcomes with hypothermic or normothermic machine perfusion were assessed against SCS here. Methods: A search in MEDLINE, EMBASE and Scopus was conducted in February 2021. Primary studies investigating ex vivo machine perfusion were assessed for the following outcomes: morbidity, ICU and hospital stay, graft and patient survival rates and relative costs. Meta-analysis was performed to obtain pooled summary measures. Results: Thirty-four articles involving 1742 patients were included, of which 20 were used for quantitative synthesis. Odds ratios favoured hypothermic machine perfusion (over SCS) with less early allograft dysfunction, ischaemic cholangiopathy, non-anastomotic strictures and graft loss. Hypothermic machine perfusion was associated with a shorter hospital stay and normothermic machine perfusion with reduced graft injury. Two randomized clinical trials found normothermic machine perfusion reduced major complication risks. Conclusion: Machine perfusion assists some outcomes with potential cost savings. Abstract : Due to the scarcity of donor livers, many centres are increasing their usage of extended-criteria allografts. It is thought that machine perfusion can preserve such 'marginal' high-risk grafts better than conventional static cold storage (SCS) by alleviating ischaemia–reperfusion injury, thereby reducing post-transplantation complications. The objective of this systematic review was to analyse existing literature to compare recipient outcomes of livers preserved with hypothermic (HMP) or normothermic machine perfusion (NMP) with those of livers preserved with SCS.